Developing a thermo-regulative system for nonwoven textiles using microencapsulated organic coconut oil - ÖNER, ERHAN; KAHRAMAN, MEMET VEZİR (SAGE PUBLICATIONS INC, 2022)
Organic coconut oil was investigated as a bio-based phase change material in core, and melamine formaldehyde was used as shell material to fabricate microencapsulated phase change material for thermo-regulation in nonwoven textiles. The microcapsules were synthesized using in situ polymerization method. The produced microcapsules (microencapsulated phase change material) were applied by knife coating in different ratios (1:5 and 1.5:5; MPCM: coating paste by wt.) to 100% polypropylene nonwoven, porous, and hydrophilic layer of a laminated, spunbond, and double-layer fabric. The coated layer was confined within two layers of the fabric to develop a thermo-regulative system on the nonwoven fabric to regulate the body temperature in surgeries. The two layers were composed by applying heat (140 degrees C) and pressure (12 kg/cm(2)). Organic coconut oil, the fabricated microcapsule, and the composite fabrics were characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, and scanning electron microscopy. Scanning electron microscopy results revealed that spherical and uniform microcapsules were obtained with an approximate particle size of 2-6 mu m. Differential scanning calorimetry results indicated that microencapsulated phase change material and the composite fabrics possessed significant melting enthalpies of 72.9 and 8.4-11.4 J/g, respectively, at peak melting temperatures between 21.6 and 22.8 degrees C within human comfort temperature range. The utilization of coconut oil as a phase change material and the composite integration of this phase change material to a nonwoven fabric bring forward a novelty for future applications.
Keywords: Bio-based phase change material; coconut oil; microencapsulation; nonwoven textile; thermo-regulation; PHASE-CHANGE MATERIALS; FORMALDEHYDE; MICROCAPSULES; RESIN; ACID; PERFORMANCES; PH